2021
DOI: 10.3389/fvets.2021.669815
|View full text |Cite
|
Sign up to set email alerts
|

Histomorphometric Quantitative Evaluation of Long-Term Risedronate Use in a Knee Osteoarthritis Rabbit Model

Abstract: Osteoarthritis (OA) treatment is a major orthopedic challenge given that there is no ideal drug capable to reverse or stop the progression of the OA. In that regard, bisphosphonates have been proposed as potential disease-modifying drugs due to their possible chondroprotective effect related to obtaining a greater subchondral bone quality. However, their effectiveness in OA is still controversial and additionally, there is little evidence focused on their long-term effect in preclinical studies. The aim of thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 62 publications
(121 reference statements)
0
0
1
Order By: Relevance
“…In contrast to these findings, long term systemic treatment of rabbits with bisphosphonates did not protect against subchondral bone remodeling or PTOA severity ( Fernandez-Martin et al, 2021 ; Fernandez-Martin et al, 2020 ). This indicated that bisphosphonate therapy may be better utilized as a pre-emptive or early therapy against developing PTOA rather than mitigating further progression of established PTOA.…”
Section: Pathogenesis Of Ptoa – Chronic Aberrant Loading Of Cartilagecontrasting
confidence: 73%
“…In contrast to these findings, long term systemic treatment of rabbits with bisphosphonates did not protect against subchondral bone remodeling or PTOA severity ( Fernandez-Martin et al, 2021 ; Fernandez-Martin et al, 2020 ). This indicated that bisphosphonate therapy may be better utilized as a pre-emptive or early therapy against developing PTOA rather than mitigating further progression of established PTOA.…”
Section: Pathogenesis Of Ptoa – Chronic Aberrant Loading Of Cartilagecontrasting
confidence: 73%